conventional radiography and computed tomography to cervical spine study of adult horses - review - Souza, Livia Pasini de [UNESP]; Sesoko, Natalia Ferreira [UNESP]; Santos, Roberta Valeriano dos [UNESP]; Evangelista, Felipe Carvalho [UNESP]; Machado, Vania Maria de Vasconcelos [UNESP]; Vulcano, Luiz Carlos [UNESP] (Univ Federal Rural Pernambuco, 2011)
The imaging is essential to aid the diagnosis of horses that have performance decrease associated with any pain or clinical signs related to the vertebral column. Radiography is the first imaging examination performed in these cases, particularly for disorders affecting the cervical region. However, this technique has limitations when the study of subtle changes due to the overlapping of adjacent structures. Computed tomography is a new diagnostic method in Brazil for the study of bone disorders in horses, but it is of great diagnostic value associate with the radiographic examination in order to provide an accurate assessment of the study area, owing to superiority in image quality when compared to conventional radiography. The aim of this study is increase and update knowledge of diagnostic imaging available to investigate cervical disorders in horses.
Keywords: Horses; Cervical region; Radiology; Tomography